2008
DOI: 10.1681/asn.2007030263
|View full text |Cite
|
Sign up to set email alerts
|

DHEA Induces 11β-HSD2 by Acting on CCAAT/Enhancer-Binding Proteins

Abstract: 11␤-Hydroxysteroid dehydrogenase (11␤-HSD) type 1 and type 2 catalyze the interconversion of inactive and active glucocorticoids. Impaired regulation of these enzymes has been associated with obesity, diabetes, hypertension, and cardiovascular disease. Previous studies in animals and humans suggested that dehydroepiandrosterone (DHEA) has antiglucocorticoid effects, but the underlying mechanisms are unknown. In this study, DHEA treatment markedly increased mRNA expression and activity of 11␤-HSD2 in a rat cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 53 publications
(53 reference statements)
3
45
0
Order By: Relevance
“…In addition to cooperative effects between GR and C/EBP in the regulation of gene transcription, glucocorticoids have an effect by inducing some of the C/EBP isoforms. Glucocorticoids have been shown to regulate C/EBPs in different tissues [McCarthy et al, 2000;Delany et al, 2001;Roesler, 2001;Balazs et al, 2008]. Similar to our findings, previous studies have also indicated an induction of C/EBPb (but not C/EBPa) by glucocorticoids in osteoblasts and kidney [McCarthy et al, 2000;Delany et al, 2001;Balazs et al, 2008].…”
Section: Stromstedtsupporting
confidence: 91%
“…In addition to cooperative effects between GR and C/EBP in the regulation of gene transcription, glucocorticoids have an effect by inducing some of the C/EBP isoforms. Glucocorticoids have been shown to regulate C/EBPs in different tissues [McCarthy et al, 2000;Delany et al, 2001;Roesler, 2001;Balazs et al, 2008]. Similar to our findings, previous studies have also indicated an induction of C/EBPb (but not C/EBPa) by glucocorticoids in osteoblasts and kidney [McCarthy et al, 2000;Delany et al, 2001;Balazs et al, 2008].…”
Section: Stromstedtsupporting
confidence: 91%
“…The transcription factor CCAAT/enhancer-binding protein C/EBP family is a key mediator of metabolic and inflammatory signalling. It has been reported that dehydroepiandrosterone caused the upregulation of C/EBP-b but did not affect C/EBP-a, whereas C/EBP-a is a strong activator of 11b-HSD1, and C/EBP-b acts in an opposite way and preferentially stimulates 11b-HSD2 expression 37 . Notably, dehydroepiandrosterone-mediated stimulation of 11b-HSD2 involves the activation of phosphoinositide 3-kinase (PI3K)/Akt pathway.…”
Section: Discussionmentioning
confidence: 94%
“…An increased 11β-HSD1 expression and activity was observed in mouse 3T3-L1 adipocytes that were cultivated in medium containing fructose as the only carbohydrate source instead of glucose [35]. As a possible explanation for the elevated expression, an increased ratio of the transcription factors C/EBPα to C/EBPβ, reported earlier to be involved in the transcriptional regulation of 11β-HSD1 [138,139], was detected. Moreover, 3T3-L1 adipocytes differentiated in fructose containing medium had elevated expression of GLUT5, thus further enhancing fructose uptake and stimulating 11β-HSD1 expression and activity.…”
Section: Effect Of Fructose On 11β-hsd1 Expression and Activitymentioning
confidence: 95%
“…TNF-α promotes ceramide and FFAs release in systemic circulation [136,137], causing insulin resistance of peripheral tissues and organs [60,138]. TNF-α induces IRS-1(Ser 307 ) phosphorylation to decrease insulin sensitivity in adipose tissue [28,139]. A series of serine kinases, including ERK, c-JNK and p38 MAPK [39] can sense lipid metabolites, and inflammatory cytokines in adipocytes and skeletal muscle cells, the activation of which under TNF-α further disturbs the functions of local tissues and organs [139].…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation